Analysis of the sensitivity and reproducibility of the Basso, Beattie, Bresnahan (BBB) scale in wistar rats (Clinics, 2008)
OBJECTIVE: To evaluate the sensitivity and reproducibility of the Basso, Beattie, Bresnahan functional scale in the assessment of the locomotor capacity of rats after spinal cord injury. METHODS: Thirty male Wistar rats underwent laminectomy and mild, moderate or severe spinal cord contusions using the New York University Weight Drop Impactor. The mice were followed for 28 days, after which time each rat was placed in an 80x80x30 cm³ clear box lined with a blue non-slippery material and stimulated to move. Their movement was video-recorded by three digital cameras operating simultaneously. Identical copies of the edited videos were given to six independent evaluators who were blinded with regards to the degree of injury severity. Each evaluator made a determination of the locomotor capacity of the rats using the Basso, Beattie, Bresnahan functional scale. RESULTS: We determined the sensitivity of the method to differences among the evaluators as well as between the results achieved on the left and right hind paws of rats subjected to either mild, moderate or severe injuries by comparing the functional outcomes and reproducibility using non-parametric correlation tests. CONCLUSIONS: The Basso, Beattie, Bresnahan scale showed high reproducibility and satisfactory sensitivity for identifying mild injuries; satisfactory reproducibility and non-satisfactory sensitivity for moderate injuries; and reduced reproducibility and non-satisfactory sensitivity for severe injuries.